Consistency in constitutional design and its effect on democracy. Issue 6 (18th August 2019) - Fruhstorfer, Anna
ABSTRACT: Does the art of crafting and amending a constitution lead to an internal consistency among constitutional provisions, and if so, what effect does that have on countries' democratic performance? Drawing from theoretical claims on the separation of power and electoral legitimacy, this article develops a concept that identifies the institutional characteristics of consistency and inconsistency in the constitutional design with the example of the presidency. Empirically, this concept is focused on aligning or counterbalancing the mode of presidential election and the de jure power of the president. Based on a comparative perspective of republican parliamentary and semi-presidential systems, the article focuses on the empirical trends of consistent and inconsistent design and addresses their effect on democratic development. The findings show a balance between consistent and inconsistent design in terms of quantity. The influence on democratization varies considerably across different measures but I find significant support for a positive effect of inconsistency on liberal democracy, freedom, horizontal accountability and the rule of law.